Study Policies of Two Ministries in Implementing the Education Curriculum in Indonesia - Tamami, Badrut; Hilmy, Masdar; Sahri, Iksan Kamil; Ramlan, Siti Rosilawati (LETIGES, 2024)
This study aims to analyze the policies of two ministries, namely the Ministry of Religious Affairs (Kemenag) and the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) at the elementary and junior high school levels, in implementing the education curriculum in Indonesia. This study is qualitative with a Systematic Literature Review (SLR) approach. Data in the form of scientific articles collected from 2015–2024. The data collection technique used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) procedure. The study results show significant differences in the curriculum's structure, focus, and approach implemented by the two ministries. The Ministry of Religious Affairs curriculum emphasizes integrating religious values ​​with science. In contrast, the curriculum under the Ministry of Education and Culture focuses more on developing general competencies based on science and technology. However, there is potential to synergize the policies of the two ministries to create a more holistic curriculum, which not only builds intellectual intelligence but also strengthens religious character and national insight. This study recommends harmonizing inter-ministerial policies through more intensive coordination mechanisms and adapting inclusive curricula according to the needs of the multicultural society in Indonesia. This study focuses on policy analysis at the ministerial level and does not directly evaluate school or district-level curriculum implementation. This study contributes by comparatively analyzing the education policies of two ministries in Indonesia, which have not been widely discussed in previous studies. This study also highlights the importance of policy synergy in building an integrative and adaptive curriculum to the challenges of education in a culturally and religiously diverse society.